Hubungan Kecemasan dan FoMO (Fear of Missing Out) dengan Nomophobia pada Mahasiswa Fakultas Keperawatan - Dela Melani; Yunisman Roni; Ade Dilaruri (Universitas Karya Husada Semarang, 2025)
Introduction: Smartphones can have positive and negative impacts on their users. Generally, smartphone use among the community is difficult to control, causing dependence on smartphone use or known as nomophobia. Objective: This study aims to determine the relationship between anxiety and FoMO in the Faculty of Nursing, University of Riau. Method: This study is a quantitative study using a descriptive correlational design and a cross-sectional approach. The research sample was 235 respondents from the Faculty of Nursing, University of Riau using the stratified random sampling technique. The instruments used in this study were the No Mobile Phone Phobia Questionnaire (NMP-Q), Fear of Missing Out Scale (FoMOS) and HARS (Hamilton Anxiety Rating Scale). The analysis using the alternative kolmogorov smirnov test. Results: The majority of respondents experienced moderate nomophobia as many as 129 (54.9%), high anxiety as many as 121 (51.5%) and high FoMO as many as 123 (52.3%) students. There was a significant relationship between anxiety and nomophobia with a p value = 0.001 <0.05 and there was a significant relationship between FoMO and nomophobia obtained a p value = 0.000 <0.05. Conclusion: The higher the anxiety and FoMO, the higher the nomophobia, conversely, the lower the anxiety and FoMO, the lower the nomophobia in students.